DEVELOPMENT OF JP-BASED TEACHING MATERIALS WITH STEM-C APPROACH THROUGH THE INTEGRATION OF QUR'AN VERSES IN IMPROVING STUDENTS' PROBLEM-SOLVING ABILITIES - Fitra, Rahmat; Susilawati, Anggi (Jurnal Visipena, 2025)
Cultivating holistic abilities is one of the most important things, especially in today's era with such rapid global influence. Education in schools must not only contribute to building cognitive abilities, but also students must be taught to build character and problem-solving skills through questioning, especially in science learning. This study aims to develop a question network (JP)-based teaching module using the STEM-C approach through the integration of Al-Qur'anic verses. The type of research used in this study is Research and Development (R&D) with the Borg and Gall model with a product test design in the study using one group pretest-posttest. The research sample consisted of 110 students from junior high schools in Aceh. The data in this study were analyzed using the N-gain test to see the improvement in students' problem-solving abilities. Based on the results of the analysis that has been done, it shows a significant increase in students' problem-solving abilities, with the average pre-test score obtained at 37.51 in the low category increasing to 85.08 in the very high category for the post-test score, while the increase from the N-gain test was obtained at 0.75 in the high category. This increase occurred in all problem-solving indicators, such as focusing on problems, drawing situations, planning solutions, implementing plans, and evaluating answers. Then the character values ​​of students obtained also increased from 32.2 in the low category to 82.6 in the high category. In addition, the JP-based teaching module with the STEM-C approach through the verses of the Qur'an proved effective in improving students' problem-solving abilities and forming positive characters with an average response value obtained at 3.17 and a percentage of 79.25%. The development of JP-based teaching materials using a STEM-C approach, integrated with Qur’anic verses, is expected improve students’ problem-solving abilities and foster better character.